A Pilot Study on Bolus Administration of Recombinant Staphylokinase for Coronary Artery Thrombolysis - Vanderschueren, S; Collen, D; Van de Werf, F (Thrombosis and Haemostasis, 1996)
Recombinant staphylokinase (Sak) is a highly fibrin-specific thrombolytic agent but the optimal dose and mode of administration remain to be defined. Intravenous (i.v.) infusion over 5 min of 20 mg Sak in 12 patients with acute myocardial infarction induced complete coronary patency (TIMI perfusion grade 3) in 7 patients (58%) within 60 min. In 3 of the 5 patients with no or suboptimal flow (TIMI grade 0,1 or 2) at 60 min, an additional 10 mg i.v. bolus of Sak resulted in TIMI grade 3 flow at 90 min. No major treatment-related complication occurred. Residual fibrinogen and α2-antiplasmin levels at 90 min were 110 ± 6.0% and 98 ±4.1% (mean ± SEM) of baseline, respectively. Median antibody-related Sak-neutralizing activity was low at baseline (0.0 μg/ml) and after 1 week (0.5 μg/ml) but increased from day 10 on (to 4.0 μg/ml).Thus, bolus thrombolysis with Sak may induce efficient coronary artery recanalization while preserving circulating fibrinogen and α2-antiplasmin. Comparative trials of coronary thrombolysis with double-bolus Sak appear to be warranted.